2018
DOI: 10.1111/jpn.13051
|View full text |Cite
|
Sign up to set email alerts
|

Feeding hay rich in water‐soluble carbohydrates improves ruminal pH without affecting rumination and systemic health in early lactation dairy cows

Abstract: Forages rich in water-soluble carbohydrates (WSC) might be an ideal energy source during early lactation, as they provide both energy for milk production and structural fibre to promote chewing and rumen buffering. Thus, the aim was to investigate feeding strategies based on high-quality hay rich in WSC with graded amounts of concentrate on ruminating behaviour, ruminal pH and systemic health variables.Twenty-four Simmental cows were randomly allocated to four groups beginning 10 days before until 28 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…В фазу раздоя коров высокие энергетические затраты на молокообразование не могут быть полностью покрыты за счет питательных веществ, поступающих с кормом Взаимосвязь усвояемости рациона и эффективности корма у крупного рогатого скота изучена недостаточно [4]. Корма, обогащенные углеводными добавками, могут быть идеальным источником энергии в период ранней лактации, поскольку они обеспечивают как энергию для производства молока, так и структурную клетчатку, способствующую жеванию и буферизации рубца [5]. Крахмал и сахар имеют функцию обеспечивать энергией животных и микроорганизмы, находящиеся в преджелудках жвачных, помимо этого участвуют при синтезе белка [6].…”
Section: ведениеunclassified
“…В фазу раздоя коров высокие энергетические затраты на молокообразование не могут быть полностью покрыты за счет питательных веществ, поступающих с кормом Взаимосвязь усвояемости рациона и эффективности корма у крупного рогатого скота изучена недостаточно [4]. Корма, обогащенные углеводными добавками, могут быть идеальным источником энергии в период ранней лактации, поскольку они обеспечивают как энергию для производства молока, так и структурную клетчатку, способствующую жеванию и буферизации рубца [5]. Крахмал и сахар имеют функцию обеспечивать энергией животных и микроорганизмы, находящиеся в преджелудках жвачных, помимо этого участвуют при синтезе белка [6].…”
Section: ведениеunclassified
“…58,59 In two independent studies, we also found no risk of SARA as a result of feeding WSC-rich ryegrass hay at WSC intake levels up to 3.3 kg day −1 , even in combination with starch (WSC of 2.7 kg day −1 plus starch of 3.6 kg day −1 , exceeding 300 g kg −1 DM in starch plus WSC). 60 One reason why WSC-rich ryegrass hay alone or with starch did not lead to SARA is the still high level of peNDF contained in hay, which helps maintain a high chewing index, 61 as well as the high CP content of the WSC-rich hay, adding to the ruminal buffering capacity. 60 Although feeding starch-rich diets is commonly associated with a decreased bacterial diversity and species richness, 62 the effects of feeding WSC-rich hay were less pronounced.…”
Section: Characterization Of Plant Storage Carbohydratesmentioning
confidence: 99%
“…60 One reason why WSC-rich ryegrass hay alone or with starch did not lead to SARA is the still high level of peNDF contained in hay, which helps maintain a high chewing index, 61 as well as the high CP content of the WSC-rich hay, adding to the ruminal buffering capacity. 60 Although feeding starch-rich diets is commonly associated with a decreased bacterial diversity and species richness, 62 the effects of feeding WSC-rich hay were less pronounced. 13 Nevertheless, significant shifts on all taxonomic levels have been observed, demonstrating that WSC-rich ryegrass hay supports fructanolytic bacteria such as Pseudobutyrivibrio ruminis, whereas starch degrading genera such as Ruminobacter are inhibited.…”
Section: Characterization Of Plant Storage Carbohydratesmentioning
confidence: 99%
“…Starch fermentation increases the amount of propionate produced in the rumen, which increases the availability of glucose in the blood through hepatic gluconeogenesis (Klevenhusen, 2019). The inclusion of fat in the diet of ruminants improves energy efficiency by directly supplying long-chain fatty acids for fatty acid synthesis (Bhatt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%